Transformation of Green Economic Recovery Based on Photovoltaic Solar Canopy - Untung Rahardja; Po Abas Sunarya; Ninda Lutfiani; Marviola Hardini; Siti Nurindah Sari (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Electrical energy has become a significant need to run the country's economy. Especially during the Covid-19 pandemic, teaching and learning activities were in the main realized at home. As a result, the national electricity demand has increased significantly. The solar power plant in the marine is also a good alternative in areas that are constrained by the lack of land as a Solar Power Plant development site. This research is motivated by the need for solar power plants using sustainable photovoltaic (PV) technology, aiming to accelerate the improvement of the quality and competence of lecturers and students in carrying out sustainable Renewable Energy (REY) research by applying the Merdeka Belajar-Kampus Merdeka (MBKM) model. The research method begins by conducting a Systematic Literature Review (SLR), which can support the relevance of sustainable REY research. The result of this research is a literature review of solar canopy PV, which is modified to be valuable in courses in the form of a sustainable REY Semester Learning Plan for one semester. From our current research, we hope that in future research, solar panel technology can not only be applied on land but also more broadly. For example, it can be applied in marine waters so that the use of solar panels can be used in many places.